PENYELESAIAN PERKAWINAN DI BAWAH UMUR (Analisis Hakim di Pengadilan Agama) - Ribat Ribat (Institut agama islam negeri Padangsidimpuan, 2016)
Marriage under the marriage age is the contoversial issue in muslim society. Al-Qur’an ang Sunnah did not explain about the marriage age explicitly. Eventhought, the Muslim scholars did not state the marriage age. So, that is why the Muslim countries regulate the marriage age on different ways. Indonesia states that the marriage age is 19 years old for man and 16 years old for women, Malaysia is 18 years old for man and 16 years old for women, Aljazair and Bangladesh are 21 years old for man and 18 years old for women. Marriage under the marriage age has the positive (maslahat) and negative effects (mafsadat). This article tries to understand the prohibition of marriage age from al-maslahat perspective by using sociological-law analysis.